2017
DOI: 10.4103/ijmr.ijmr_717_16
|View full text |Cite
|
Sign up to set email alerts
|

Dyslipidaemia & oxidative stress in patients of psoriasis

Abstract: Background & objectives:Psoriasis is a recurrent hyper-proliferative skin disease which is often associated with free radical generation, abnormal lipid metabolism and increased inflammatory secretion that induce cardiovascular risk in these patients. The present study was intended to evaluate serum lipids, lipoprotein and oxidants-antioxidants status and to establish their relationship with atherogenic risk markers [oxidized low-density lipoprotein (oxLDL) and high-sensitivity C-reactive protein (hsCRP)] in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Psoriasis is associated with an atherogenic lipid profile and significant lipid abnormalities have been noted even during 5 years preceding onset of psoriasis [35]. Similarly, another study reported that the mean oxLDL levels in patients with psoriasis were significantly higher than those of healthy controls [36].…”
Section: Dyslipidemiamentioning
confidence: 97%
“…Psoriasis is associated with an atherogenic lipid profile and significant lipid abnormalities have been noted even during 5 years preceding onset of psoriasis [35]. Similarly, another study reported that the mean oxLDL levels in patients with psoriasis were significantly higher than those of healthy controls [36].…”
Section: Dyslipidemiamentioning
confidence: 97%
“…More ROS produced owing to the inflammatory process may lead to the formation of lipid oxidation products such as malondialdehyde. Increased serum malondialdehyde was correlated with disease severity [85], and ROS also elevated the levels of protein oxidation products such as pyrrolized protein, protein carbonyl compounds, and advanced oxidation protein products [86].…”
Section: Oxidative Stress and Platelet Activationmentioning
confidence: 99%
“…Psoriasis is a chronic skin disease characterized by scaling, thickening and erythema of the skin, which is probably the most prevalent immune-mediated skin disease in adults [25]. Recent studies show that some mutations may lead to an abnormally increased activity of the immune system and, consequently, to increased inflammation and accompanying oxidative stress [26].…”
Section: Discussionmentioning
confidence: 99%